Studi tentang Budaya Organisasi dan Dampaknya terhadap Employee Well-Being - Diyanah Fatin; Naufal Ramadan; Ramadhan Pasaribu (Kampus Akademik Publiser, 2025)
The influence of organizational culture on employee well-being in the workplace is the subject of this study. It is thought that the physical, mental and emotional well-being of employees is greatly influenced by organizational culture, which consists of the values, norms, beliefs and practices embraced by a company. A descriptive study was used as the research method. To improve retention and productivity, this study shows how important it is to build a corporate culture that supports employee wellness. This study emphasizes how important organizational culture is as an important factor that determines employee performance and contributes to previous research on human resource management.